Exploratory research analysis on emissions generated in internal combustion engines - Rocha, Márcio Andrade (2018)
It is common knowledge that internal combustion engines have the function of transforming thermal energy into useful mechanical work. During the combustion process of the fuel and air mixture (heat generation) a quantity of gases are produced and released into the environment by the exhaust system of these engines. When these machines were invented, their creators might not have had the notion that the generated gases would be aggressors to nature. The constant population growth, the increasing demand for the use of these engines and observations of the impact in nature, among them the health and greenhouse effects, evidenced mainly from the end of the last century, led scientists to study the problem related to gaseous emissions from these machines. The present work aims to study and evaluate the emissions of internal combustion engines, their consequences both to the human health and to the environment, the evolution of government legislation and also the control mechanisms implemented to reduce these pollutants. The applied methodology is a qualitative and exploratory study of bibliographic character of theoretical and experimental works that were presented in master's dissertations, doctoral theses, scientific articles and websites of companies specialized in the subject.